Measuring changes of students' problem-solving skills for citizen science projects that integrated in ecology courses: Stacking analysis techniques in Rasch model - Susbiyanto Susbiyanto; Topik Hidayat; Hertien Koosbandiah Surtikanti; Riandi Riandi (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Authentic and practice-based learning approaches to develop students' problem-solving skills in the context of complex environmental problems are needed. This study aims to measure how students' problem-solving skills have changed through Citizen Science Project that integrated in ecology courses using stacking analysis techniques in the Rasch model. The method in this research used a descriptive quantitative approach by comparing the level of change in problem solving skills after the intervention of learning activities with citizen science projects through pre-test and post-test. There were thirty students participating in total. The results of the Rasch analysis show that the average problem-solving skills score is 0.73, with a Cronbach Alpha value of 0.97, person reliability of 0.97, and item reliability of 0.88. These values show very good interaction between students and question items, as well as very good consistency in student answers. Logit item measures of changes in students' problem solving skills show that almost students experienced an increase in their ability to understand component of the questions construction. Students in this research were able to sharpen their problem-solving skills through the citizen science projects they completed.Abstrak. Pendekatan pembelajaran yang autentik dan berbasis praktik untuk mengembangkan keterampilan pemecahan masalah mahasiswa dalam konteks permasalahan lingkungan yang kompleks diperlukan. Penelitian ini bertujuan untuk mengukur bagaimana perubahan kemampuan pemecahan masalah mahasiswa melalui proyek citizen science yang diintegrasikan dalam mata kuliah ekologi dengan menggunakan teknik analisis stacking dalam model Rasch. Metode dalam penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan membandingkan tingkat perubahan keterampilan pemecahan masalah setelah diberikan intervensi kegiatan pembelajaran dengan proyek citizen science melalui pre-test dan post-test. Total ada tiga puluh mahasiswa yang berpartisipasi. Hasil analisis Rasch menunjukkan rata-rata skor kemampuan mahasiswa sebesar 0,73, dengan nilai Cronbach Alpha sebesar 0,97, person reliabilitas sebesar 0,97, dan reliabilitas item sebesar 0,88. Nilai-nilai tersebut menunjukkan interaksi yang sangat baik antara mahasiswa dengan item soal, serta konsistensi jawaban mahasiswa yang sangat baik. Proyek citizen science yang dilakukan oleh mahasiswa dalam penelitian ini efektif dalam meningkatkan kemampuan pemecahan masalah mereka.